The History of Bone Islamization in the XVII-XIX Centuries and the Impact on Society's Religious Traditions - Moh Ashif Fuadi; Usman Usman (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
This article aims to describe Islam in Bone, history of entry, development, and influence on the religious traditions of the Bone community. This article uses historical research methods with four stages: heuristics, verification, interpretation, and historiography. The results of the research: 1. Acceptance of Islam in Bone is the main role of the King who ruled for approximately three months, namely King La Tenri Pale, who was the XI king of the Bone kingdom in the 17th century AD. Officially, Islam was accepted by the people of Bone on November 23, 1611, AD or 20 Ramadan 1020 H when King XII ruled, namely La Tenri Ruwa Matinroe ri Bantaeng or known by his Islamic name as Sultan Adam. 2. The development of Islam began to spread to the XIII king who ruled, namely La Maddaremmeng or known as Muhammad Salih (1631-1640 AD). 3. The influence of Islam that emerged in the Bone community, namely, marriage, birth, and death. It is this religious tradition that gets the influence of Islamic teachings on the people of Bone.